Evaluating hand hygiene knowledge, attitudes, and practices among healthcare workers in post-pandemic H1N1 influenza control: a cross-sectional study from China - Hong, Qin; Xu, Yuling (Frontiers in Public Health, 2024)
Background This study evaluates the knowledge, attitudes, and practices (KAP) of hand hygiene among healthcare workers, crucial for preventing healthcare-associated infections (HAIs) in medical facilities. Methodology This cross-sectional study assessed hand hygiene KAP among healthcare workers across various settings in Hubei, China utilizing a stratified random sampling approach from, December 25, 2023-to-April 25, 2024. A bilingual electronic survey, adapted from validated tools, was disseminated via email and social media to ensure a broad reach. Participants included diverse healthcare professionals who met specific inclusion criteria. Responses were analyzed using R software, employing descriptive and inferential statistics to identify key predictors of hand hygiene behavior and to confirm the reliability of the survey instrument. Results The survey of 2,265 healthcare workers revealed that 77% demonstrated comprehensive knowledge of hand hygiene, 80% exhibited positive attitudes, and 94% practiced effective hand hygiene. Notable findings include a significant understanding of hand hygiene’s role in preventing respiratory illnesses (58%) and HAIs (41% agreed, 39% unsure). High compliance in practices like washing hands for at least 20 s was evident (84%), though gaps in confidence about hand hygiene techniques were noted (33% confident, 56% unsure). Binary logistic regression analysis indicated that younger healthcare workers (21–30 years) were more likely to exhibit both knowledge (OR = 7.4, 95% CI = 1.44–136, p = 0.059) and positive attitudes (OR = 4.48, 95% CI = 1.73–11.8, p < 0.001) compared to other age groups. Significant associations were found between higher income levels and positive attitudes toward hand hygiene (OR for ≥80,000 = 3.19, 95% CI = 2.05–5.02, p < 0.001), and between knowledge and practices, suggesting that well-informed individuals are more likely to adhere to recommended practices. Conclusion The findings reveal robust hand hygiene knowledge but uncover critical confidence gaps among healthcare workers, urging immediate, targeted educational interventions to fortify adherence and prevent infection outbreaks.